Weight loss-independent changes in human growth hormone during water-only fasting: a secondary evaluation of a randomized controlled trial - Horne, Benjamin D.; Anderson, Jeffrey L.; May, Heidi T.; Bair, Tami L.; Le, Viet T.; Iverson, Leslie; Knowlton, Kirk U.; Muhlestein, Joseph B. (Frontiers in Endocrinology, 2025)
IntroductionWater-only fasting for one day or more may provide health benefits independent of weight loss. Human growth hormone (HGH) may play a key role in multiple fasting-triggered mechanisms. Whether HGH changes during fasting are independent of weight loss and how basal HGH and HGH change relate to other fasting-induced changes are unknown.MethodsApparently healthy individuals (N=30) were randomized by Latin square to begin two days with either 24-hour water-only fasting or a control of 24-hour ad libitum eating. On day 2, subjects were crossed over to control (if day 1 was fasting) or fasting (if they ate on day 1). HGH, weight, and other parameters were measured at baseline and at the end of the first and second days.ResultsBaseline HGH had median 0.50 ng/mL for females (n=20) and 0.04 ng/mL for males (n=10), and correlated inversely with weight, glucose, insulin, and triglycerides and positively with changes in insulin and HOMA-IR. The 24-hour fasting-induced HGH change was uncorrelated with weight loss (r= 0.01, p=0.98), but correlated with changes in glucose, HGB, and IGF-1. The percent increase in HGH was greater (p<0.001) for lower (females ≤0.15 ng/mL, males ≤0.05 ng/mL) vs. higher baseline HGH (median: 1,225% vs. 50.3%, respectively). Subjects with lower baseline HGH had a trend to greater reduction of HOMA-IR (median: -6.15 vs. -1.35 for lower vs. higher HGH, respectively, p=0.08).ConclusionsFasting increased HGH and the HGH changes were independent of weight loss. Basal HGH and fasting-induced HGH changes correlated inversely with cardiometabolic risk factors.Clinical Trial Registration: clinicaltrials.gov, identifier NCT01059760.